Microchannel Heat Sinks—A Comprehensive Review - Usman Ghani; Muhammad Anas Wazir; Kareem Akhtar; Mohsin Wajib; Shahmir Shaukat (Electronic Materials)
An efficient cooling system is necessary for the reliability and safety of modern microchips for a longer life. As microchips become smaller and more powerful, the heat flux generated by these chips per unit area also rises sharply. Traditional cooling techniques are inadequate to meet the recent cooling requirements of microchips. To meet the current cooling demand of microelectromechanical systems (MEMS) devices and microchips, microchannel heat sink (MCHS) technology is the latest invention, one that can dissipate a significant amount of heat because of its high surface area to volume ratio. This study provides a concise summary of the design, material selection, and performance parameters of the MCHSs that have been developed over the last few decades. The limitations and challenges associated with the different techniques employed by researchers over time to enhance the thermal efficiency of microchannel heat sinks are discussed. The effects on the thermal enhancement factor, Nusselt number, and pressure drop at different Reynold numbers in passive techniques (flow obstruction) i.e., ribs, grooves, dimples, and cavities change in the curvature of MCHSs, are discussed. This study also discusses the increase in heat transfer using nanofluids and how a change in coolant type also significantly affects the thermal performance of MCHSs by obstructing flow. This study provides trends and useful guidelines for researchers to design more effective MCHSs to keep up with the cooling demands of power electronics.